Куземинське укріплення в Більському городищі - Гавриш, П.Я. (Археологія, 2003)
У статті розглядається проблема Куземинського укріплення в системі оборонних споруд Більського городища скіфської доби на Полтавщині. Автор спростовує існування цього укріплення на підставі власних польових досліджень та критичного аналізу опублікованих матеріалів. В начале XX в., во время полевых археологических исследований на Бельском городище, В. А. Городцов нанес на общий план укрепление у с. Куземин, которое будто бы примыкает к валу Большого Бельского городища со стороны р. Ворскла. Никаких конкретных материалов, характеризующих это укрепление, опубликовано не было. В послевоенные десятилетия исследователи Бельского городища Г.Т. Ковпаненко, Б.Н. Граков, А.А. Моруженко, Б.А. Шрамко поддержали мнение В.А. Городцова о существовании Куземинского укрепления как составной части фортификационной системы Бельского городища. Б.А. Шрамко обосновал функциональное назначение Куземинского укрепления как прикрытия торговой пристани-порта г. Гелона на берегу р. Ворсклы.
Однако анализ опубликованных в научной литературе материалов и данные разведок не позволяют автору согласиться с мнением о существовании в оборонительной системе Бельского городища отдельного Куземинского укрепления. Некорректным следует признать использование случайно обнаруженных в 1952 г. где-то на территории с. Куземин античных амфор, которых никто из исследователей не видел, в качестве аргумента в пользу определения несуществующего Куземинского укрепления как прикрытия торговой пристани на берегу р. Ворсклы и наличия там складских помещений греческих купцов в V—III вв. до н. э.
Не подтвердилось и наличие культурного слоя на предполагаемой площади укрепления. At the beginning of the 20,h century during excavations on the Bels’ke hr11 fort V.A. Gorodtsov plotted on the general plan a fortification near the village of Kuzemin, as if it bordered with a bank of the Velyke Bels’ke hill fort on the side of the River Vorskla. There was no publications of materials giving concrete expression to this fortification. After the II World War researchers of the Bels’ke hill fort such as G.T. Kovpanenko, B.N. Grakov, A. A. Morudjenko, B.A. Shramko supported Gorodtsov’s opinion about the Kuzemins’ke fortification as a part of fortification of the Bels’ke hillfort. Shramko grounded a purpose of the Kuzemins’ke fortification to protect a trade wharves of the town of Helon on a bank of the River Vorskla.
However analysis of published materials in the scientific literature and database of prospecting give no opportunity to the author being of the opinion that separate Kuzemins’ke fortification was in existence in a system of fortification of the Bels’ke hillfort. Uncorrected turning to account is to admit according to ancient Greek amphorae found somewhere in territory of the village of Kuzemyn in 1952. Nobody of researchers saw they but they are drawn as an argument in favor of existence a non-existent Kuzemins’ke fortification as a protection of the trade wharves on a bank of the River Vorskla and being warehouses of Greek merchants from the 5th to the 3rd centuries BC there. Pointed cultural layer wasn’t found on a hypothetical ground of fortification.